2014
DOI: 10.1016/j.ijsu.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative ultrasound in conservative surgery for non-palpable breast cancer after neoadjuvant chemotherapy

Abstract: The emplacement of a readily echodetectable metal marker before NACT makes IOUS excision feasible in an increasing number of complete clinical responses, with the excision of small amounts of breast tissue and a high percentage of conservative breast surgery. This technique requires surgeons to be trained, but has the advantage of a reduced use of other hospital services, better planning of operating theatres, and less discomfort for patients, which means that it is attractive and indeed recommendable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…In concordance with our study, Chan et al [18] and Sharek et al [19] stated that the most widely adopted [20], reported that wire-guided localization is the standard procedure but is a timeconsuming procedure because it requires the expertise of an experienced radiologist and it is uncomfortable and usually stressful for the patient. Moreover, it may be associated with a high number of positive margins, increases in local recurrences, inadvertent wire displacement during patient transfer, surgical positioning, or during postprocedure mammography and a poor cosmetic result while intraoperative ultrasound (IOUS) excision, an attractive and recommendable practice as an alternative to other excision techniques in patients with complete clinical responses after NACT as wire localization.…”
Section: Discussionsupporting
confidence: 92%
“…In concordance with our study, Chan et al [18] and Sharek et al [19] stated that the most widely adopted [20], reported that wire-guided localization is the standard procedure but is a timeconsuming procedure because it requires the expertise of an experienced radiologist and it is uncomfortable and usually stressful for the patient. Moreover, it may be associated with a high number of positive margins, increases in local recurrences, inadvertent wire displacement during patient transfer, surgical positioning, or during postprocedure mammography and a poor cosmetic result while intraoperative ultrasound (IOUS) excision, an attractive and recommendable practice as an alternative to other excision techniques in patients with complete clinical responses after NACT as wire localization.…”
Section: Discussionsupporting
confidence: 92%
“…The same is true for patients with tumors that are clipped with ultrasound guidance before neoadjuvant chemotherapy who subsequently have a complete radiologic response. The advantages of sonographically detectable clips in postneoadjuvant breast‐conserving surgery were recently shown by Ramos et al When a lesion is detectable solely by MRI, sonographically detectable clip deployment can again simplify subsequent localization. Postneoadjuvant localization in the situation of a residual tumor that is not adjacent to the clip may be especially problematic and should be preoperatively performed by the radiologist.…”
Section: Discussionmentioning
confidence: 96%
“…Esta técnica también se ha demostrado de utilidad como método de exéresis en aquellas pacientes a las que se les había administrado quimioterapia neoadyuvante y presentaban LNP o, incluso, respuesta completa de la enfermedad, sólo persistiendo el marcador metálico colocado previo a la administración de la quimioterapia. La tasa de reintervenciones publicadas por márgenes afectos ha sido del 6,6% evitando en un 8,6% la reintervención de estas pacientes cuando se realizaba conjuntamente el estudio de los márgenes con la eco y el estudio intraoperatorio por el patólogo 43 . En general, la tasa de afectación de márgenes publicados con esta técnica varía desde un 0% descrito por Paramo hasta el 9% publicado por otros autores, con un valor predictivo negativo para la afectación de estos márgenes de un 92,8% [44][45][46][47][48] .…”
Section: Discussionunclassified